2018
DOI: 10.3892/mmr.2018.9269
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in necroptosis during ALDH2‑mediated protection against high glucose‑induced H9c2 cardiac cell injury

Abstract: The aim of the present study was to investigate whether necroptosis occurs in high glucose (HG)-induced H9c2 cardiac cell injury and whether the activation of aldehyde dehydrogenase 2 (ALDH2) can inhibit necroptosis. H9c2 cardiac cells were treated with 35 mM glucose to establish a HG-induced cell injury model. Alda-1 (20 µM), a specific activator of ALDH2 and necrostatin-1 (Nec-1, 100 µM), an inhibitor of necroptosis were used to treat H9c2 cardiac cells under HG conditions. Cell viability was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…Liang et al firstly reported the contribution of necroptosis in HG-induced injury in cardiac cells and role of Nec-1 in reducing cytotoxicity, oxidative stress and dissipation of mitochondrial membrane potential (MMP) [ 39 ]. Similar results were obtained by later researches in both cardiac cells and endothelial cells [ 38 , 40 , 41 ]. However, current studies only provide an elusive description on this Nec-1 protective effect, and the underlying molecular mechanism remains to be investigated.…”
Section: Role Of Nec-1 In Disease Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…Liang et al firstly reported the contribution of necroptosis in HG-induced injury in cardiac cells and role of Nec-1 in reducing cytotoxicity, oxidative stress and dissipation of mitochondrial membrane potential (MMP) [ 39 ]. Similar results were obtained by later researches in both cardiac cells and endothelial cells [ 38 , 40 , 41 ]. However, current studies only provide an elusive description on this Nec-1 protective effect, and the underlying molecular mechanism remains to be investigated.…”
Section: Role Of Nec-1 In Disease Modelssupporting
confidence: 91%
“…Besides, Han et al found that Nec-1 can enhance leukemia cell apoptosis induced by Shikonin [ 96 ], showing an anti-cancer effect; Jie et al found that Nec-1 could specifically induce neutrophils apoptosis rather than blockage [ 97 ], which implies an anti-inflammatory effect. Despite researches mentioned above, some researchers claim that Nec-1 does not affect apoptosis [ 38 , 48 ], which is probably RIA. When apoptosis is mainly RIP1-dependent, Nec-1 inhibits RIP1 kinase activity and formation of complex Ⅱa, and thus apoptosis is blocked; however, when apoptosis is RIP1-independent, Nec-1 has no inhibitory effect.…”
Section: Role Of Nec-1 In Disease Modelsmentioning
confidence: 99%
“…2009 , 2016 ). Down-regulation of the gene can induce inflammation, apoptosis and necrosis by the activation of ROS pathway ( Fang et al., 2018 ; Liang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dihydroethidium (DHE) probe (Beyotime, Shanghai, China) was used to measure ROS generation in H9c2 cells, as previously described [13]. Briefly, cells were adjusted to 1.5×10 5 cells per well and cultured in a 24-well culture plate.…”
Section: Methodsmentioning
confidence: 99%